Human-Nature Relationship in Hardy’s The Woodlanders - Lamichhane, Hari Krishna (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
This article examines human-nature relationship in Thomas Hardy’s novel The Woodlanders. It examines how Hardy shows environment’s role in nourishing human beings and giving them knowledge. This article, in particular, studies the situations of the characters Grace Melbury, Fitzipiers and Mrs. Charmond. In the novel, Hardy dramatizes how place determines the ‘making’ and ‘unmaking’ of an individual especially through the character of Grace Melbury. The novel deals with the problematic aspects of being uprooted from the place. The characters with the rootedness to place have the easier survival, fixed geographical and cultural identity and the other who have not rootedness with the geographical location neither get fixed social/cultural identity nor assimilate with the place properly. Lack of assimilation with the place makes the characters suffer. In this sense, the novel has highly emphasized the sense of place in it.